2022
DOI: 10.25105/imar.v20i2.12554
|View full text |Cite
|
Sign up to set email alerts
|

The role of Social Media Marketing in increasing Brand Awareness, Brand Image and Purchase Intention

Abstract: In recent years, social media is not only used for social interaction activities, but is also used as a medium for doing business. Especially at this time when the whole world is facing the covid 19 pandemic, where most countries make decisions about closing and restricting several physical places, which have been used to carry out business activities, entrepreneurs are trying to optimize digital media and social media as a strategy to market their products. This study aims to determine the role of social medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
3
4
0
Order By: Relevance
“…This research is the same as previous research in that there is a direct influence between E-WoM on brand trust (Siregar et al, 2021); (Mou & Benyoucef, 2021); (Zanjabila et al, nd, 2023) The seventh hypothesis regarding brand image has a positive and significant effect on purchasing decisions with a t-value of 3.594 and a p-value of 0.000 < 0.05, so it can be interpreted that H7 is accepted. This research is in accordance with previous research which stated that there is a positive and significant influence of brand image on purchasing decisions (Sanny, 2020); (Faisal & Ekawanto, 2021); (Fataya and... 2023) The eighth hypothesis regarding brand trust has a positive and significant effect on purchasing decisions with a t-value of 2.957 and a p-value of 0.003 < 0.05, so it can be interpreted that H7 is accepted. This research is in accordance with previous research which stated that there is a positive and significant influence of brand trust on purchasing decisions (Pandjaitan & Faila, 2019); (Hidayati, 2022); (Subiyakto et al, 2023) The ninth hypothesis is that social media marketing has a positive and significant influence on purchasing decisions mediated by brand image with a t-value of 2.590 and a p-value of 0.010 <0.05, so it can be said that H9 is accepted.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This research is the same as previous research in that there is a direct influence between E-WoM on brand trust (Siregar et al, 2021); (Mou & Benyoucef, 2021); (Zanjabila et al, nd, 2023) The seventh hypothesis regarding brand image has a positive and significant effect on purchasing decisions with a t-value of 3.594 and a p-value of 0.000 < 0.05, so it can be interpreted that H7 is accepted. This research is in accordance with previous research which stated that there is a positive and significant influence of brand image on purchasing decisions (Sanny, 2020); (Faisal & Ekawanto, 2021); (Fataya and... 2023) The eighth hypothesis regarding brand trust has a positive and significant effect on purchasing decisions with a t-value of 2.957 and a p-value of 0.003 < 0.05, so it can be interpreted that H7 is accepted. This research is in accordance with previous research which stated that there is a positive and significant influence of brand trust on purchasing decisions (Pandjaitan & Faila, 2019); (Hidayati, 2022); (Subiyakto et al, 2023) The ninth hypothesis is that social media marketing has a positive and significant influence on purchasing decisions mediated by brand image with a t-value of 2.590 and a p-value of 0.010 <0.05, so it can be said that H9 is accepted.…”
Section: Discussionsupporting
confidence: 91%
“…This research is not in accordance with previous research which stated that there is a positive and significant influence of social media marketing on brand trust (Irawan & Hadisumarto, 2020); (Haryanto & Wulandari, 2022); (Winarso, 2023) The fifth hypothesis regarding E-WoM has a positive and significant effect on brand image by obtaining a t-value of 13.601 and a p-value of 0.000 < 0.05, which can be interpreted as H5 being accepted. This research is the same as previous research which described the existence of E-WoM as having a positive and significant effect on brand image (Nuseir, 2019); (Putra & Gupron, 2020); (Faisal & Ekawanto, 2021) The sixth hypothesis is that E-WoM has a positive and significant influence on brand trust with a t-value of 13.185 and a p-value of 0.041 < 0.05, so it can be said that H6 is accepted. This research is the same as previous research in that there is a direct influence between E-WoM on brand trust (Siregar et al, 2021); (Mou & Benyoucef, 2021); (Zanjabila et al, nd, 2023) The seventh hypothesis regarding brand image has a positive and significant effect on purchasing decisions with a t-value of 3.594 and a p-value of 0.000 < 0.05, so it can be interpreted that H7 is accepted.…”
Section: Discussionsupporting
confidence: 54%
“…The researcher therefore failed to reject the hypothesis concluding that SMM through eWOM has a significant positive influence on brand awareness in the education services sector in Lusaka, Zambia. The results corroborate with the study by Faisal and Ekawanto (2021) which showed that SMM activities in terms of WOM have a positive impact on brand awareness. More so, Thuy and Long Open Journal of Business and Management (2023) also found that eWOM through SMM positively impact customers' brand awareness.…”
Section: As Shown Insupporting
confidence: 90%
“…It leverages the power of social networks to connect with a large and engaged audience. For businesses and organizations, utilizing social media marketing can significantly enhance brand visibility, foster customer engagement, and boost sales (Faisal & Ekawanto, 2022). Choosing the right social media platforms to reach and engage with customers through social media marketing effectively is essential (Agrawal & Trivedi, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%